The China threat : memories, myths, and realities in the 1950s - Tucker, Nancy Bernkopf (Columbia University Press, 2012)
Nancy Bernkopf Tucker confronts the coldest period of the cold war-the moment in which personality, American political culture, public opinion, and high politics came together to define the Eisenhower Administration's policy toward China. A sophisticated, multidimensional account based on prodigious, cutting edge research, this volume convincingly portrays Eisenhower's private belief that close relations between the United States and the People's Republic of China were inevitable and that careful consideration of the PRC should constitute a critical part of American diplomacy. Tucker c.